2020
DOI: 10.1016/j.ijid.2020.09.1449
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the cycle threshold values of SARS-CoV-2 polymerase chain reaction and total severity score of computerized tomography in patients with COVID 19

Abstract: Highlights There are limited number of studies analyzing viral load in COVID19 patients and any data that compare viral load to chest computerized tomography (CT) severity. There are limited number of studies that give the amount of SARS-CoV-2 RNA in clinical specimens by reporting cycle threshold (Ct) value for RT-PCR. The total stress score (TSS) was suggested to quantify pulmonary inflammation and correlate to the clinical classifications. TSS is a quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 16 publications
2
39
1
Order By: Relevance
“…For other viral illnesses, the initial viral load has been associated with disease severity [ 18 , 19 ], however, a consensus has not been reached regarding COVID-19. To the best of our knowledge, 11 studies have shown that nasopharyngeal SARS-CoV-2 Ct are not associated with, or predict, COVID-19 severity [ 13 , 14 , 15 , 20 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. However, only six of them analyzed samples with >100 cases, the majority included only hospitalized patients, and the follow-up was relatively short.…”
Section: Discussionmentioning
confidence: 99%
“…For other viral illnesses, the initial viral load has been associated with disease severity [ 18 , 19 ], however, a consensus has not been reached regarding COVID-19. To the best of our knowledge, 11 studies have shown that nasopharyngeal SARS-CoV-2 Ct are not associated with, or predict, COVID-19 severity [ 13 , 14 , 15 , 20 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. However, only six of them analyzed samples with >100 cases, the majority included only hospitalized patients, and the follow-up was relatively short.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that Ct values may indirectly reflect the viral load in a given patient, our results suggest that older SARS-CoV-2-infected individuals have higher viremia at diagnosis ( Tom and Mina, 2020 ), which may at least partly explain more severe course of the disease and worse prognosis ( Karahasan Yagci et al, 2020 ). A relationship between lower Ct values and higher clinical severity has already been found years ago in patients with various upper respiratory tract infections, caused by adenovirus, human metapneumovirus, and parainfluenza virus ( Fuller et al, 2013 ).…”
Section: Resultsmentioning
confidence: 96%
“…Here, the key is to have access to patient oro- or nasopharyngeal samples in viral transport medium (VTM) that display low Ct values in the quantitative real time RT-PCR assays. The association of the viral load estimated by qRT-PCR with COVID severity is controversial [21, 22], and qRT-PCR-generated Ct values of viral genes are not true indicators of the viral load owing to a large number of variables in sample collection and processing and hence could be deceptive at times. Therefore it is important to try several VTM samples that display Ct values below 30.…”
Section: Resultsmentioning
confidence: 99%